موقف النقاش من الإسرائيليات في تفسيره شفاء الصدور (Al-Naqqash’s Position in relation to Israelite sources in his Tafsir Shifa’ al-Sudur) - بن سيف الـمُهَيري حمدة بنت خليفة; الأطرش رضوان جمال (Journal of Islam in Asia (E-ISSN 2289-8077), 2017)
الملخّص تفسير شفاء الصدور، لأبي بكر محمد بن الحسن النقاش 351ه. موسوعة علمية حوى تفسيراً بالمأثور وبالرأي متعدد الألوان، ومنها تفسيره بالإسرائيليات، وقد عرفت فيه بالإسرائيليات، وأهميتها في التفسير، ونشأتها ومواقف العلماء منها، ولاسيما مواقف الصحابة منها، وأقسامها الثلاثة: ما وافق شرعنا الحنيف، ثم ما خالفه، ثم المسكوت عنها، وضربت لذلك أمثلة مما ورد عند النقاش وقارنتها بما ورد في كتب المسلمين عنها القدامى والمعاصرين، وكتب النصارى مثل الأناجيل الأربعة وإنجيل برنابا وإنجيل لوقا وكتاب مورمون وكتب اليهود كالتلمود والمشنى والتوراة السامرية والزبور ومزامير داود والكتاب المقدس لموريس بوكاي، كما اطلعت على مواقع إلكترونية عن الكتب المقدسة وشروحها وتعليقات علماء اللاهوت عندهم، لتكون حجة عليهم من كتبهم، وكان هذا من الجديد في هذا البحث الذي لم أسبق إليه بهذه المقارنة فيما أعلم لأن الدراسات السابقة التي اطلعت عليها كانت تعتمد على ما ورد في كتب المسلمين دون غيرهم، وأنهيت البحث بمقارنة ما ورد عن اليهود من تفسير ألم البقرة وعلاقتها بمدة ملك الرسول r لاعتمادهم على حساب الجُمّل، وبينت خطأهم في ذلك. الكلمات المفتاحية: منهج، النقاش، الإسرائيليات، التفسير. Abstract The Qur’anic exegesis Shifa’ al-Sudūr is an encyclopedic work of Abu Bakar Muhammad ibn al-Ḥasan al-Naqqash (d. 351 AH.). It is based on various sources of exegesis such as the transmitted (al-ma’thūr), the rational (al-ra’y) and Israelite traditions. This paper defines the Israelite traditions, their significance in the field of exegesis, their origin, and the position of the Muslim Scholars in relation to them, especially the position of the Prophet’s (s.a.w.) Companions. The Israelite traditions are classified into three categories: those which are compatible with our Shariah, those which oppose the Shariah, and those which are neither opposing nor agreeing. The researcher presented examples of these types from the Shifa’ al-Sudūr and compared them with those mentioned in the Muslim scholars’ classical and contemporary works, Christian books such as the four bibles, The Gospel of Barnabas, the Gospel of Luke, Book of Mormon, Jewish books such as The Talmud, The Mishnah, The Samaritan Torah, The Zabur, The Psalms of David, and the book of Maurice Bucaille. The researcher also looked into various websites on the holy books, its expositions, and the comments of theologians in order to create a strong case against them from their own books. This mode of study is the first of its kind in this field, because the previous studies were mainly based on the Muslim works. The researcher made a comparison between Jewish traditions concerning various stories in Surah al-Baqarah and Muslim exegesis of the Surah in this work. Keywords: Approach, Al-Naqqash, Israelite Traditions, Exegesis.